Examining the psychological process of developing consumer-brand relationships through strategic use of social media brand chatbots. (March 2023) - Lin, Jhih-Syuan (Elaine); Wu, Linwan
Abstract: As brands increasingly integrate artificial intelligence (AI)-enabled automation as part of their communication efforts, marketers have employed social media brand chatbots to provide personalized responses to consumers and facilitate relationship building. However, how specific facets of consumer–brand relationships may be manifested in the process of consumer–brand interaction via social media brand chatbots warrants further investigation. Hence, the current research develops a conceptual model to examine how perceived contingency, a defining psychological determinant of social media brand chatbots, determines consumer−brand relationship outcomes via different motivational experiences and consumer engagement. Based on the survey conducted in the U.S. (N = 491), the findings reveal that perceived contingency is positively related to gratifications of information seeking, social interaction, and entertainment, while information seeking and social interaction lead to enhanced consumer engagement. In addition, consumer engagement helps deepen brand intimacy, strengthen affective commitment, and increase chatbot-related behavioral intention and purchase intention. The findings further show that social-interaction gratification and consumer engagement are crucial components that underline how consumers' perception of contingency can foster strong, affect-laden brand relationships when marketers capitalize on the conversational capabilities of social media brand chatbots. Theoretical and practical implications, as well as limitations and directions for future research, are discussed. Highlights: Perceived contingency enhances engagement through fulfilling types of gratification. Consumer engagement positively contributes to consumer-brand relationship outcomes. Perceived contingency of brand chatbots facilitates consumer-brand relationships. Social gratification and engagement are crucial relationship-building components.